PIK3CA Mutations as a Molecular Target for Hormone Receptor-Positive, HER2-Negative Metastatic Breast Cancer - Fusco, Nicola; Malapelle, Umberto; Fassan, Matteo; Marchiò, Caterina; Buglioni, Simonetta; Zupo, Simonetta; Criscitiello, Carmen; Vigneri, Paolo; Dei Tos, Angelo Paolo; Maiorano, Eugenio; Viale, Giuseppe (Frontiers in Oncology, 2021)
Despite the significant achievements in the diagnosis and treatment of metastatic breast cancer, this condition remains substantially an incurable disease. Over the past few years, several clinical studies aimed to identify novel molecular targets, therapeutic strategies, and predictive biomarkers to improve the outcome of women with metastatic breast cancer. Among these, targeting phosphoinositide 3 kinase (PI3K)/AKT/mammalian target of rapamycin (mTOR) pathway has shown significant results. Overall, approximately 40% of hormone receptor (HR)+/HER2- metastatic breast cancers harbor alterations affecting the PI3K/Akt pathway. This pathway is a major target in oncogenesis, as it regulates growth, proliferation, cell survival, and angiogenesis. Lately, the pharmacologic targeting of PIK3CA in HR+/HER2- metastatic breast cancer has allowed for significant benefits, particularly after the occurrence of endocrine resistance. In particular, the orally available alpha-selective PIK3CA inhibitor alpelisib has shown interesting results and has been approved in this setting. However, it is crucial to adopt the best methodology to perform an optimal patients’ selection. Next-generation sequencing panels can be employed to cover several different alterations simultaneously. Clinically relevant PIK3CA alterations may be detected in several biospecimens, including tissue samples and liquid biopsy. In this review, we provide an overview of the role of PIK3CA in breast cancer and of the characterization of its mutational status for appropriate clinical management of the patients.